Peningkatan Kinerja Perorangan dan Kelompok Terhadap Kinerja Organisasi Melalui Pelatihan dan Pengembangan Pada PT.ABC - Taswiyah Taswiyah; Diah Astuti; Ghaznawie Ihyamukti; Riri Anbar Baiduri (Student Research Journal, 2024)
This study aims to determine the impact of employee training and skills development programs and team building activities on individual and group performance, as well as their impact on overall organizational performance. The research method was carried out qualitatively descriptively through Google Scholar journal access for national, accredited, and international journals with the object of observation of PT.ABC. The results of the research on employee training and skills development programs and team building activities can provide significant benefits for employees and affect overall organizational performance.